The influence of rifamycin decontamination on incorporation of autologous onlay bone grafts in rats: A histometric and immunohistochemical evaluation. Issue 5 (May 2015) - Taşdemir, Ufuk; Özeç, İlker and Esen, Hacı Hasan and Avunduk, M. Cihat
Highlights: The effect of decontamination solutions on bone healing should be considered. Rifamycin is a suitable solution for bone decontamination. Bone morphogenetic protein-2 (BMP-2) expression was induced by rifamycin solution. Abstract: Objective: Although it has been shown that rifamycin is an effective agent for bone graft decontamination, no information exists on the effects of rifamycin decontamination on bone graft incorporation. The aim of this study was to evaluate the influence of rifamycin decontamination on the incorporation of autologous onlay bone grafts quantitatively. Design: In 30 rats, a standardized 5.0-mm-diameter bone graft was harvested from the right mandibular angle, contaminated with saliva, decontaminated with rifamycin solution, and augmented to the left as an onlay graft. Ten animals were sacrificed at 7, 14, and 21 days after surgery. In the control group (10 rats), the onlay grafts were neither contaminated nor decontaminated, and the rats were sacrificed at 21 days after surgery. Histological slides were prepared from each grafted site for both immunohistochemistry analysis (bone morphogenetic protein-2 (BMP-2) and vascular endothelial growth factor (VEGF) antibodies) and histometric analysis. Images obtained from the graft incorporation area with the light microscope were transferred to a PC, and they were evaluated using Clemex PE 3.5 image analysis software. Results: The grafts were fully incorporated in all specimens. The results showed that rifamycin decontamination has no detrimental effect on graft incorporation and the findings revealed a tendency for earlier revascularization and osteogenesis in the decontamination group. Data were analyzed using variance analysis and Tukey's test. Conclusions: Rifamycin decontamination has no detrimental effect on autogenous graft incorporation, and it can be used for graft decontamination with confidence.